Natriuresis-Guided Diuretic Therapy in Acute Heart Failure: A Meta-Analysis of Diuretic Efficacy - Syed Wajihullah Shah, Abuzar Khan (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: Acute Heart Failure (AHF) is a major cause of hospitalisation and mortality. While loop diuretics are the mainstay of treatment, relying solely on clinical signs for dose adjustments can delay effective therapy. Natriuresis offers an objective marker for diuretic response. This meta-analysis evaluates the effectiveness and safety of natriuresis-guided diuretic therapy compared to standard care. Objective: To assess whether natriuresis-guided diuretic therapy improves clinical outcomes in patients recovering from acute heart failure. Materials and Methods: A systematic review and meta-analysis were conducted per PRISMA and Cochrane guidelines. PubMed, Embase, and Web of Science were searched for relevant trials up to February 2025. Studies included randomised or non-randomised trials comparing natriuresis-guided diuretic therapy to standard care in AHF patients. Primary outcomes included natriuresis (mmol at 24 and 48 hours) and diuresis (L at 48 hours); secondary outcomes were weight loss (kg at 48 hours), length of stay (days), hypotension (systolic BP < 90 mmHg), and hypokalemia (serum K⁺ < 3.5 mmol/L). Data was analysed using RevMan 5.4. Results were presented as mean difference (MD) or risk ratio (RR) with 95% confidence intervals, and heterogeneity was assessed using the I² statistic. Results: Four trials with 831 patients were included. Natriuresis-guided therapy significantly improved natriuresis at 24 hours (MD: 83.66 mmol, P < 0.00001) and 48 hours (MD: 132.27 mmol, P = 0.0003). Diuresis at 48 hours also increased (MD: 1.35 L, P < 0.00001). Weight loss showed a non-significant increase (MD: 0.49 kg, P = 0.11). Hospital stay was reduced (MD: -0.80 days, P = 0.005). No significant differences were observed for incidence of hypotension (RR: 0.80, P = 0.60) or hypokalemia (RR: 1.03, P = 0.92). Conclusion: Natriuresis-guided diuretic therapy improves natriuresis, diuresis and shortens hospital stay in AHF patients, with a safety profile comparable to standard care. Keywords: Acute Heart Failure, Natriuresis, Diuretics, Hypokalemia, Hypotension